Development of an automated method for generating patient-specific mandible reconstruction plates based on mandibular landmarks - Hanekom, Werner (Stellenbosch : Stellenbosch University, 2025)
Hanekom, W. 2025. Development of an automated method for generating patient-specific mandible reconstruction plates based on mandibular landmarks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/26e3a257-f4ff-4254-a54b-af57a783aef5